Skillnader mellan länsstyrelser – takhöjd för häst - Mårtensson, Gabriella (2014)
To ensure that animals are treated well and kept in environments fitted for them, Sweden has animal welfare legislation. One of the requirements in the legislation is that horses are kept in spaces that has a ceiling height that measures at least 1,5 * the height at the withers of the horse, but always a minimum of 2,2 m. But a minor derivation can be accepted from these measurements if certain criteria are fulfilled. If the ceiling height is to low the ventilation in the stable can be negatively affected. It can also affect the posture of the horse and may increase the risk of the horse being injured. Horses are prey animals that flee in situations of potential danger. If a horse perceives danger in a stable they may hit the ceiling when trying to flee, if the ceiling height is too low. The horse can also hit the ceiling when swinging its´ head. The competent authorities that control animal welfare in Sweden on regional level are the county administrative boards. As control authorities they perform controls on animal housings. If the housing does not meet up with the legislation standards the county administrative boards can issue injunctions to the responsible person. If this person does not agree with the injunctions it can be appealed.